Effect of composition on phase formation, microstructure and dielectric properties of sol-bonded PZTN-PZT ceramics - Sangsubun C. (2014)
The PZTN sol-powder was synthesized from a triol sol-gel process, while the ball milled PZT powder prepared from the reagent grade oxides of PbO, ZrO 2 and TiO2 powders. The sol and balled milled powders were mixed at a ratio of 30:70, 50:50 and 70:30 by weight. The results showed that at a composition of 70:30 had the maximum density values compared with the other two compositions. X-ray diffraction analysis indicated that a single tetragonal phase was observed at all sintering temperatures for this composition (70:30). The maximum room temperature dielectric constant measured at 1 kHz was 1151 could be achieved for the ceramic sintered at 1100°C for 4 h, where the densification was optimized. © 2013 Copyright Taylor and Francis Group, LLC.